PERAN KANTIN KEJUJURAN DALAM PEMBENTUKAN KARAKTER JUJUR SANTRI DI PONDOK PESANTREN - Ai Sarah Naudyah Cahyani (IKIP Siliwangi, 2022)
One of the public educational institutions that have a role in shaping the character of the nation's successor is Islamic boarding school. One of the efforts of Islamic boarding schools in creating quality generations who have good personalities is by holding an honesty canteen. The purpose of this study was to describe the role of the honesty canteen in the formation of the honest character of students in Islamic boarding schools. The theory used in this research is honesty canteen theory, honest character theory, boarding school theory as part of public education. This study uses a qualitative approach with a descriptive method. In this study the instruments used were questionnaires, interviews, and observations. The main reason for using this instrument is to collect data on the extent of the role of the honesty canteen in the formation of the honest character of students in Islamic boarding schools and make conclusions about it by direct field observation. The research population is the residents of the Miftahul Huda Cimahi Islamic boarding school and the samples are two honesty canteen managers, two santri administrators, and ten santri. The results show that the honest character formed through the honesty canteen is to convey purchasing information to the canteen manager according to the circumstances, not to manipulate purchase data, and to dare to admit mistakes. The conclusion of this study is that the honesty canteen has an important role in the formation of honest character in students, in this case it can be seen in the formation of the honest character of students in making purchases in the honesty canteen.